Inflation uncertainty and disagreement in bond risk premia - Stefania D'Amico; Athanasios Orphanides (Federal Reserve Bank of Chicago, 2014)
This paper examines the relation between variations in perceived inflation uncertainty and bond premia. Using the subjective probability distributions available in the Survey of Professional Forecasters we construct a quarterly time series of average individual uncertainty about inflation forecasts since 1968. We show that this ex-ante measure of inflation uncertainty differs importantly from measures of disagreement regarding inflation forecasts and other proxies, such as model-based ex-post measures of macroeconomic risk. Inflation uncertainty is an important driver of bond premia, but the relation varies across inflation regimes. It is most important in the high-inflation regime early in the sample and the low-inflation regime over the last 15 years. Once the role of inflation uncertainty is accounted for, disagreement regarding inflation forecasts appears a much less important driver of bond premia.
Keywords: E37; E44; E47; C53; G12; 330; survey expectations; probabilistic forecasts; heterogeneity; inflation uncertainty; bond risk premia